Toward Information Transfer Around a Concave Corner by a Surface-Plasmon-Polariton Wave - Rajan Agrahari; Akhlesh Lakhtakia; Pradip K. Jain (IEEE Photonics Journal, 2019)
As optical interconnects employing surface-plasmon-polariton (SPP) waves are expected to enable faster communication in integrated circuits, the time-domain Maxwell equations were solved using the finite-difference time-domain method to investigate the transfer of information via a pulse-modulated carrier SPP wave around a concave corner formed by two planar metal/air interfaces. The signal is launched along the first metal/air interface and received along the second metal/air interface. The corner angle affects the intensity and the duration of the received signal, but its shape is largely independent of the corner angle of the corner. Accordingly, the signal received around the concave corner is strongly and positively correlated with the transmitted signal, a promising result for SPP-wave-based optical interconnects. The energy of the received signal varies with the frequency of the carrier SPP wave. The received signal is better correlated with the transmitted signal when the carrier frequency is higher for a fixed value of the corner angle.